2020
DOI: 10.3390/ani10061080
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, Preferences, and Palatability of Diets Containing Summer and Winter Brassica Forage in Growing Pigs: A Pilot Study

Abstract: Brassica forage may be included in pigs’ diet as a dietary fiber ingredient to reduce feeding costs, benefit gut health, immune system, reproductive traits, and welfare. However, they contain antinutritional factors which may affect feeding behavior. This study evaluated feeding behavior of growing pigs offered winter (kale and swede) and summer (turnip and forage rape) brassicas incorporated on their diets as dried ground meal. Two consecutive experiments with six growing castrated male pigs were conducted. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Based on our results, where no differences in terms of digestibility were found, and those by Figueroa et al [12], who found that forage brassica meals did not negatively affect the preference or acceptability of the diet when incorporated at 15% in growing pig diets, we expect no differences in terms of growth performance. However, this needs to be evaluated in further research.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Based on our results, where no differences in terms of digestibility were found, and those by Figueroa et al [12], who found that forage brassica meals did not negatively affect the preference or acceptability of the diet when incorporated at 15% in growing pig diets, we expect no differences in terms of growth performance. However, this needs to be evaluated in further research.…”
Section: Discussionsupporting
confidence: 65%
“…Digestion in the large intestine takes the longest amount of time (20-38 h) [48], which is why the bacteria would digest and ferment carbohydrates and proteins in greater quantities, obtaining more fatty acids in both short-and mid-chain VFAs. Additionally, turnip contains a greater amount of sugar than wheat middlings and rape, potentially changing the fermentation patterns [12,39]. Previous in vitro studies carried out with human fecal bacteria have shown that the fermentation of starch produces a higher proportion of butyric acid as a product of short-chain VFAs when compared to the fermentation of foods rich in pectin, such as brassicas that contain more than 300 g/kg DM of SF [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 450 ppm treatment, the negative effect on weight gain in the first week, followed by reduced intake, suggests an antinutritional impact in the early stages of feeding the turnip extract that was unrelated to palatability. No adverse effects on intake of feeding turnips to pigs been recorded [ 20 ]; however, reduced intakes have been noted in sheep [ 21 ]. There are potentially negative effects of glucosinolates from turnips on performance; in particular their post-ingestional derivatives may interfere with iodine uptake and the production of triiodothyronine (T3) and thyroxine (T4) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%